ABI End of Initiative - 2024 Progress Deep Dive of the sorghum, millet, groundnut, and pigeonpea breeding team from ICRISAT (Asia) - Pasupuleti, Janila (International Crops Research Institute for the Semi-Arid Tropics, 2024)
The presentation summarizes the sorghum, millet, groundnut, and pigeonpea breeding teams' efforts and progress from 2022 to 2024 through a series of questions that highlight the team's breeding achievements. It also discusses the team's successes and challenges during this period.